EVALUASI PENCAHAYAAN DAN KEBISINGAN KELAS BERDASARKAN STANDAR UTILITAS(STUDI KASUS:SD BRAWIJAYA SMART SCHOOL MALANG) - Nur Kamila, Azizah; Virnanda P, Azizah; Purna Ardhis Syahfrina, Cantika; Yuli Setyawan, Trihana; Hartini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines issues related to the physical environment of classrooms, specifically regarding lighting and noise levels that may affect students’ comfort and learning effectiveness. The objective of this study is to evaluate the lighting and noise levels in classrooms at Brawijaya Smart School Elementary School in Malang based on applicable building utility standards. The method used is a quantitative approach through field observations, employing a lux meter to measure lighting intensity and a sound level meter to measure noise levels at several points and time intervals during learning activities. The data obtained were analyzed descriptively by comparing the measurement results against national standards, namely 250–300 lux for lighting and ≤55 dB for noise. The results of the study indicate that most lighting levels remain below the recommended standards, except at certain times when the contribution of natural lighting increases. Meanwhile, noise levels consistently exceed the established thresholds, indicating suboptimal acoustic conditions.These findings indicate that lighting distribution is uneven and noise control is ineffective, which could potentially reduce students’ concentration and learning effectiveness. Therefore, improvements to the lighting and noise control systems are needed to create a more comfortable learning environment that meets standards.